(untitled) (REMUNOM, 2026)
Microalgae are present in the aquatic environment and produce bioproducts of great added value (e.g. carbohydrates, lipids, fatty acids, pigments, protein) through the conversion of solar energy into chemical energy by fixing atmospheric CO2. Therefore, microalgae biomass has many potential applications in several industries, for example, cosmetics, pharmaceuticals, agricultural biopesticides, biofuel production, and food supplements. However, microalgae harvesting involves energy consumption and high operating costs (about 30 % of the total production cost). Thus, this paper aims to review the main achievements of microalgae harvesting processes, their efficiencies, and the main advantages and disadvantages of each harvesting method. Coagulant dosage, mixing time, and velocity gradient are parameters that affect the efficiency of microalgae harvesting. Therefore, the optimal conditions of these variables will be presented in this review article. On the other hand, coagulation, followed by flotation, is influenced by attraction-repulsion forces between cells and the coagulant agent. Factors such as cell size, viability, density, possible cell damage, strain properties, sedimentation rate, the salt concentration of each algae species of microalgae, energy demand, final product, and the reuse of culture medium determine if will be necessary one or methods combined for harvesting the microalgae biomass. However, coagulation and flocculation are still relevant for the harvesting of algae cells.